Safety Assessment, In Vitro and In Vivo, and Pharmacokinetics of Emivirine, a Potent and Selective Nonnucleoside Reverse Transcriptase Inhibitor of Human Immunodeficiency Virus Type 1 - Szczech, G. M. (American Society for Microbiology, 2000)
Emivirine (EMV), formerly known as MKC-442, is 6-benzyl-1-(ethoxymethyl)-5-isopropyl-uracil, a novel nonnucleoside reverse transcriptase inhibitor that displays potent and selective anti-human immunodeficiency virus type 1 (HIV-1) activity in vivo. EMV showed little or no toxicity towards human mitochondria or human bone marrow progenitor cells. Pharmacokinetics were linear for both rats and monkeys, and oral absorption was 68% in rats. Whole-body autoradiography showed widespread distribution in tissue 30 min after rats were given an oral dose of [(14)C]EMV at 10 mg/kg of body weight. In rats given an oral dose of 250 mg/kg, there were equal levels of EMV in the plasma and the brain. In vitro experiments using liver microsomes demonstrated that the metabolism of EMV by human microsomes is approximately a third of that encountered with rat and monkey microsomes. In 1-month, 3-month, and chronic toxicology experiments (6 months with rats and 1 year with cynomolgus monkeys), toxicity was limited to readily reversible effects on the kidney consisting of vacuolation of kidney tubular epithelial cells and mild increases in blood urea nitrogen. Liver weights increased at the higher doses in rats and monkeys and were attributed to the induction of drug-metabolizing enzymes. EMV tested negative for genotoxic activity, and except for decreased feed consumption at the high dose (160 mg/kg/day), with resultant decreases in maternal and fetal body weights, EMV produced no adverse effects in a complete range of reproductive toxicology experiments performed on rats and rabbits. These results support the clinical development of EMV as a treatment for HIV-1 infection in adult and pediatric patient populations.